HTRA1 Mutations Identified in Symptomatic Carriers Have the Property of Interfering the Trimer-Dependent Activation Cascade - Uemura, Masahiro; Nozaki, Hiroaki; Koyama, Akihide; Sakai, Naoko; Ando, Shoichiro; Kanazawa, Masato; Kato, Taisuke; Onodera, Osamu (Frontiers in Neurology, 2019)
Background—Mutations in the high-temperature requirement A serine peptidase 1 (HTRA1) cause cerebral autosomal recessive arteriopathy with subcortical infarcts and leukoencephalopathy (CARASIL). Most carriers for HTRA1 mutations are asymptomatic, but more than ten mutations have been reported in symptomatic carriers. The molecular differences between the mutations identified in symptomatic carriers and mutations identified only in CARASIL patients are unclear. HTRA1 is a serine protease that forms homotrimers, with each HTRA1 subunit activating the adjacent HTRA1 via the sensor domain of loop 3 (L3) and the activation domain of loop D (LD). Previously, we analyzed four HTRA1 mutant proteins identified in symptomatic carriers and found that they were unable to form trimers or had mutations in the LD or L3 domain. The mutant HTRA1s with these properties are presumed to inhibit trimer-dependent activation cascade. Indeed, these mutant HTRA1s inhibited wild-type (WT) protease activity. In this study, we further analyzed 15 missense HTRA1s to clarify the molecular character of mutant HTRA1s identified in symptomatic carriers. Methods—We analyzed twelve missense HTRA1s identified in symptomatic carriers (hetero-HTRA1) and three missense HTRA1s found only in CARASIL (CARASIL-HTRA1). The protease activity of the purified recombinant mutant HTRA1s was measured using fluorescein isothiocyanate-labeled casein as substrate. Oligomeric structure was evaluated by size-exclusion chromatography. The protease activities of mixtures of WT with each mutant HTRA1 were also measured. Results—Five hetero-HTRA1s had normal protease activity and were excluded from further analysis. Four of the seven hetero-HTRA1s and one of the three CARASIL-HTRA1s were unable to form trimers. The other three hetero-HTRA1s had mutations in the LD domain. Together with our previous work, ten of eleven hetero-HTRA1s and two of six CARASIL-HTRA1s were either defective in trimerization or had mutations in the LD or L3 domain (P = 0.006). By contrast, eight of eleven hetero-HTRA1s and two of six CARASIL-HTRA1 inhibited WT protease activity (P = 0.162). Conclusions—HTRA1 mutations identified in symptomatic carriers have the property of interfering the trimer-dependent activation cascade of HTRA1.